RANOLAZINE IN ISCHEMIC HEART DISEASE - V. P. Lupanov (Рациональная фармакотерапия в кардиологии)
Study results of a new anti-anginal drug (an inhibitor of sodium channels — ranolazine) are presented. Indications, contraindications, major clinical trials of the drug in patients with ischemic heart disease are considered.